Characterization of patients with ankylosing spondylitis in hidrokinesitherapy - a multidimensional assessment - Januário, F (2012)
OBJECTIVES: Clinical, functional and working characterization of an Ankylosing Spondylitis (AS) group of patients that perform hydrotherapy regularly in a physical and rehabilitation department. Assessment of the benefit of hydrotherapy in symptom relief, function and consumption of analgesics and non-steroidal anti-inflammatory drugs (NSAIDs). MATERIAL AND METHODS: A transversal characterization of a group of patients with SA undergoing hydrotherapy was performed. Demographic, clinical (including disease activity, function and health-related quality of life), radiographic and laboratorial data was collected. A questionnaire about working situation, presence of dyspnoea, smoking, number of sessions and benefit of hydrotherapy was applied. RESULTS: 22 patients (73% males) were enrolled in the study, mean age 55.6 ± 8.8 years, mean duration of the disease 28.0 ± 13.13 years. Apart from the axial involvement, 50% had a previous history of enthesitis, 54.5% peripheral arthritis, 18% dactylitis and 36% uveitis. At the day of assessment, 81% had low-back pain complaints (39% inflammatory rhythm), 18% oligoarthritis, 9.1% had total hip and/or knee prosthesis. The majority of the patients had active disease, accentuated functional deterioration and reduced health related quality of life. About 54.5% were retired due to disability, 18.2% were smokers and 36.4% had dyspnoea; 31.8% presented restrictive ventilatory alterations; 36.4% obstructive (predominance in the small airways); 13.6% mixed and in 18.2% the spiromety was normal. The mean total time of hydrotherapy was 13 ± 6.8 years. The patients attended a mean of 3 sessions per week and 3 series of 15 sessions per year. Of the 22.7% that performed another physical activity, 80% walked and 20% cycled. The ingestions of analgesics (p < 0.05) and NSAIDs (p < 0.01) were also reduced. CONCLUSION: A high percentage of spyrometric changes were identified. The majority of the patients are retired due to disability. The patients feel benefit with hydrotherapy, that contributed to reduction of the analgesic and NSAIDs consumption. The importance of the global systemic evaluation and multidisciplinary of the SA to optimize the therapeuthics and improve the quality of life of the patients is pointed out.